2021
DOI: 10.1002/14651858.cd012721.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Beta-blockers and inhibitors of the renin-angiotensin aldosterone system for chronic heart failure with preserved ejection fraction

Abstract: Beta-blockers and inhibitors of the renin-angiotensin aldosterone system for chronic heart failure with preserved ejection fraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 422 publications
0
22
0
4
Order By: Relevance
“…Some large-scale clinical trials abroad have also confirmed this result [ 30 , 31 ]. Some studies found that for patients who were routinely followed up at the hospital every quarter, inappropriate discharge events in ICD occur 64 days earlier than the next follow-up and remote monitoring could detect these inappropriate discharge events in time, which provided sufficient reaction time for doctors [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some large-scale clinical trials abroad have also confirmed this result [ 30 , 31 ]. Some studies found that for patients who were routinely followed up at the hospital every quarter, inappropriate discharge events in ICD occur 64 days earlier than the next follow-up and remote monitoring could detect these inappropriate discharge events in time, which provided sufficient reaction time for doctors [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the use of ACEI or ARB for direct treatment of HFpEF is not supported by evidence. A recent meta-analysis which included 10 trials investigating beta-blockers showed that, beta-blockers might reduce cardiovascular mortality in HFpEF patients, but the evidence certainty was low ( 42 ). Till now, there is no large prospective trials focusing on calcium channel blockers in HFpEF.…”
Section: Does Treatment For Arterial Stiffness Benefit In Hfpef?mentioning
confidence: 99%
“…[16] The same applies to a blockade of the sympathetic adrenergic system using beta blockers. [17,18] Because of this, it was also surprising that there was already veri able reverse remodeling in our small HFpEF cohort. The absence of signi cant changes in HFmrEF maybe due to the small sample size.…”
Section: Discussionmentioning
confidence: 92%